Phase angle is inversely related to the consumption of ultra-processed foods and positively related to the consumption of minimally processed foods by university students: a cross-sectional study - Paraskevi Detopoulou; Despoina Levidi; Olga Magni; Vassilios Dedes; Milia Tzoutzou; Evaggelia Fappa; Aristea Gioxari; Georgios Panoutsopoulos (Cambridge University Press, 2024)
Abstract Objective: Ultra-processed foods (UPF) and minimally processed foods (MPF) consumption are differentially connected to adiposity and possibly body composition. Phase angle (PhA) originates from bioelectrical impedance analysis (BIA) and is connected to cellular health. This study is the first to investigate associations between UPF/MPF consumption and PhA. Design: A cross-sectional study was conducted. Anthropometrical and BIA were performed. The Hellenic Physical Activity Questionnaire was used for physical activity evaluation, while a validated FFQ was used for dietary assessment. UPF and MPF intake (% energy) were determined according to the NOVA system. Partial correlation coefficients of PhA and dietary variables were assessed after multi-adjustment. Participants: Students were recruited (n 151, 114 women). Setting: University Results: Median and interquartile range (IQR) of PhA were 5·5° (5·1-6·4°) in the total sample, 6·8° (6·1-7·3°) in men and 5·3° (5·1-5·9°) in women (P < 0·001). The median and IQR for UPF consumption was 13·7 (8·1-33·4) % in the total sample, 23·8 (8·1-70·5) % in men and 12·9 (8·1-27·5) % in women (P < 0·001). The mean (sd) of MPF consumption was 60·2 (sd 15·7) % for the total sample, 59·1 (sd 16·4) % for men and 60·5 (sd 15·6) % for women (P = 0·720). The consumption of UPF was negatively (rho = -0·267, P = 0·002), while the consumption of MPF was positively (rho = 0·218, P = 0·010) associated with the PhA, after adjustment for age, sex, BMI and physical activity. Conclusion: PhA relates inversely to UPF and positively to MPF consumption. The observed associations possibly reflect the effects of diet on cellular health and in turn PhA.